COMPARATIVE EVALUATION BETWEEN QUALITY OF LIFE (QOL), ADVERSE EVENTS AND SURVIVAL ANALYSIS OF ISCADOR FOR THE TREATMENT OF SOLID TUMORS. - ROY, SANDEEP (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Background: Mistletoe extracts such as Iscador generally used for the treatment of various type of cancers, specifically solid cancers. It was obtained from viscum album. Objective: The present investigation was carried to find out the comparative evaluation of Quality of life (Qol), adverse events and survival analysis of Iscador for the treatment of solid cancers in data published since 2001.Methods: A comprehensive in depth search was conducted on following search engines: Pubmed and google. Two reviewers independently searched PubMed using the following Medical Subject Headings (MeSH) and text words in the database search: Randomized controlled trialâ€, iscadorâ€, Cancerâ€, Mistletoe preparationâ€, Viscum albumâ€ till April 2013. Only reports fulfilling the inclusion criteria were included in the data analysis. The search was limited to human studies, clinical trials, and English language studies.Outcome data extracted from publications as they are given. Results: We found 76 publications initially, screening of these results yielded 40 studies and remaining studies were excluded due to non-compliance with inclusion criteria. Thereafter 31 studies excluded due to insufficient data for analysis. At last 9 studies were included in the present comparative evaluation. Conclusion: Our comparative evaluation finds that Qol in cancer patients was measured by European Organization for Research and Treatment of Cancer (EORTC), Quality of Life-score 30 (QLQ-C30), Functional living index cancer (FLIC), Traditional Chinese medicine index (TCMI), karnofsky performance index (KPI), GLQ-8 and Spitzer's uniscale. In all studies adverse events related to Iscador treatment were local reaction at the injection site, chill and muscle pain, allergic skinreaction and fever. Survival analysis done by using Wilcoxon paired sample test and cox proportion hazard model and hazard ratio was reported to 0.36 to 1.32.